Journey to the forgotten river [videorecording] - Cobbler, Jonathan; Joubert, Beverly; Joubert, Dereck; National Geographic Society (Washington, D.C.).; WQED (Television station : Pittsburg, Pa.). (Washington, D.C. The Society, 1990)
An overview of the rich and varied environment of the Linyanti River and Batswana including the warriors wild animals found in the Saudi bank.
VHS.
Credits : Narrated by Peter Strauss ; Edited by Barry Nye.
Keywords: Rivers -- Africa, Southern; Animals -- Africa, Southern; Linyanti River (Batswana, Africa).